Modulation of Cell Cycle Profile by Chlorella vulgaris Prevents Replicative Senescence of Human Diploid Fibroblasts. (12th March 2013) - Saberbaghi, Tayyebeh; Abbasian, Firouz; Mohd Yusof, Yasmin Anum; Makpol, Suzana
Abstract : In this study, the effects of Chlorella vulgaris (CV) on replicative senescence of human diploid fibroblasts (HDFs) were investigated. Hot water extract of CV was used to treat HDFs at passages 6, 15, and 30 which represent young, presenescence, and senescence ages, respectively. The level of DNA damage was determined by comet assay while apoptosis and cell cycle profile were determined using FACSCalibur flow cytometer. Our results showed direct correlation between increased levels of damaged DNA and apoptosis with senescence in untreated HDFs (P < 0.05 ). Cell cycle profile showed increased population of untreated senescent cells that enter G0/G1 phase while the cell population in S phase decreased significantly (P < 0.05 ). Treatment with CV however caused a significant reduction in the level of damaged DNA and apoptosis in all age groups of HDFs (P < 0.05 ). Cell cycle analysis showed that treatment with CV increased significantly the percentage of senescent HDFs in S phase and G2/M phases but decreased the population of cells in G0/G1 phase (P < 0.05 ). In conclusion, hot water extract of Chlorella vulgaris effectively decreased the biomarkers of ageing, indicating its potential as an antiageing compound.